Laundry-Caf / Ronny Dick ... [et al.] - Dick, Ronny; Syukur, Norhidayah; Abdul Razak, Nurul Tiara; Adenan, Norhafizah (2013)
The name of our company is Laundry-Caf The business is in form of partnership which consists of four members. Each partner contributes certain amount of capital as agreed in agreement. The main business activity is Laundry-Caf with concept of self-service laundry. Apart from that, we also open up a cafe. That is why it is called Laudry-caf because it is combination of laundry and cafe. We provide customers with the best place for them to enjoy while they are waiting for their cloths. Our concept is very suitable with campus life and office workers. There are no sleeping partners and all are entitled to participate in the business management. We had agree that Ronny Bin Dick as our General Manager and Administration Manager, Norhidayah Binti Syukur as Marketing Manager, Nurul Tiara Binti Abdul Razak as Operation Manager and Norhafizah Binti Adenan as Financial Manager. The selection of General Manager is based on consensus among all the partners and selected based on experience, skills and ability of the partner. The management team will be led by the General Manager and assist by the other managers. The General Manager is responsible in planning, leading, controlling and organizing the business. The Administration Manager is responsible for the job that related to administration such as planning and arranging the remuneration schedule of salary and wages. The Operation Manager is responsible to the entire job that related to the operation and will be supervise and coordinate the operation of the business. The Marketing Manager will be responsible to create the marketing plan, identifying the customer’s need and demand, identifying the competitors, target market, market size and forecast the future market. Lastly, Financial Manager will be handled the financial matters such as preparing the budget and financial statement for expenses of each departments and controlling the flow of the money of the organization.